Analysis of the Impact of Fiscal Decentralization on Education Output on the Islands of Java and Bali 2010-2019 - Astuti, Hanida Widi; Sasana, Hadi; Sugiharti, Retno (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
Fiscal decentralization has been implemented since 2001 with the aim of providing greater capacity to the community for the services that the government provides to the community. This research aims to analyze the impact of education spending, GDP per capita, student to teacher ratio, number of schools on the average student test scores on the islands of Java and Bali in 2010-2019. This research uses panel data sourced from BPS, ministry of education and culture. The method used is the random effect model. From the test results, spending in the education sector has a significant effect on the average student test scores, the ratio of students per teacher, GDP per capita and the number of schools do not have a significant effect on the average test score. Overall, modelling with REM produces an value of 9.3 percent. The results of this research show that increasing average students test scores can be done by increasing spending on education.